Upaya Pencegahan Peningkatan Osteoarthritis pada Lansia Di Posyandu Kleben Desa Gedongan, Kec. Colomadu, Kab. Karanganyar - Pristianto, Arif; Saputri, Fauzia Riska; Lestari, Amelia Tirta; Aulidya, Sarah Citra; Nuraeni, Wilda Arifia; Maharani, Devita Putri (ISAS (Indonesian Society of Applied Science), 2023)
Osteoarthitis is a degenerative disease that occurs in several joints. Osteoarthitis is most often found in the Kleben elderly posyandu, Gedongan Village, Kec. Colomadu is knee osteoarthritis. The cause of knee osteoarthritis can be trauma or obesity. Apart from that, heavy activity or work also causes excessive work on the joints. There are many factors that influence the occurrence of knee osteoarthritis, namely age, gender and genetics. Therefore, efforts to prevent the increase in knee osteoarthritis are very necessary to reduce pain and increase range of motion. By carrying out counseling using hold relax stretching exercises and carried out independently for 3 weeks with a dose of 7x counts for 6-8x repetitions, results were obtained between pre and post, namely changes in reducing pain and increasing rage of motion in the elderly.